2019
DOI: 10.1111/rda.13403
|View full text |Cite
|
Sign up to set email alerts
|

Low‐mobility sperm phenotype in the domestic turkey: Impact on sperm morphometry and early embryonic death

Abstract: Contents The sperm mobility assay measures the ability of sperm to swim through a dense layer of Accudenz®, and the sperm mobility phenotype has been shown to predict fertility and other sperm performance traits in roosters and turkeys. In this study, we examined turkey sperm morphometry and rates of early embryonic death associated with high‐ and low‐mobility semen. We also assessed whether the hypo‐osmotic stress test, which evaluates the structural integrity of the sperm plasma membrane, may be used as a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, sperm swimming durations were longer in internally fertilizing species than in externally fertilizing species, as is typical in fishes (Gwo et al ., 2009). There are a few studies indicating that midpiece size is positively correlated with sperm swimming velocity (Gil et al ., 2009; Firman & Simmons, 2010; Smith & Ryan, 2010; Fitzpatrick et al ., 2016); and negative or no correlations have also been detected (Malo et al ., 2006; Mossman et al ., 2009; Cramer et al ., 2015; Manier et al ., 2019). The relationship between midpiece size and sperm motility (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sperm swimming durations were longer in internally fertilizing species than in externally fertilizing species, as is typical in fishes (Gwo et al ., 2009). There are a few studies indicating that midpiece size is positively correlated with sperm swimming velocity (Gil et al ., 2009; Firman & Simmons, 2010; Smith & Ryan, 2010; Fitzpatrick et al ., 2016); and negative or no correlations have also been detected (Malo et al ., 2006; Mossman et al ., 2009; Cramer et al ., 2015; Manier et al ., 2019). The relationship between midpiece size and sperm motility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…longer flagellum) than those with lower levels of sperm competition (the other three polygynous species) (Fitzpatrick et al ., 2009; Kleven et al ., 2009; Tourmente et al ., 2011), although several studies have demonstrated that sperm competition is unrelated to sperm velocity and length (Stockley et al ., 1997; Langen et al ., 2019). Third, the midpiece that contains mitochondria would also be longer in internally fertilizing species because sperms with higher velocities and/or longer swimming durations might be more energy demanding (Cardullo & Baltz, 1991; Parker, 1993; Gil et al ., 2009; Firman & Simmons, 2010; Smith & Ryan, 2010), although this relationship is still controversial (Malo et al ., 2006; Mossman et al ., 2009; Evans, 2011; Cramer et al ., 2015; Manier et al ., 2019). An elongated midpiece is mainly represented in internally fertilizing teleost fish (van Deurs, 1975; Pitnick et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These conclude positive effects of antioxidant treatments on, for example, sperm motility and that treatments may elevate live birth rate (but data quality for live births was considered 'low', owing to complex interpretation of many predictors (our interpretation)). In addition, ROS aside, low-mobility sperm in domestic turkeys, Meleagris gallopavo, have a higher rate of early embryonic death, but genetic and mechanistic underpinnings to this finding are unknown [52]. Similar effects on sperm swimming performance were confirmed to be genomic by Alavioon et al [53], but judgement is suspended regarding which specific genes predicted motility effects.…”
Section: Sperm Performance Ros and Seminal Antioxidationmentioning
confidence: 99%
“…Investigating the genetic and epigenetic mechanisms underlying spermatogenesis allows us to better understand the entire process of sperm production and maturation on the molecular level. Sperm motility is the basic parameter of semen quality [ 4 , 31 , 32 , 33 ] in both mammals and birds [ 34 ], including turkeys [ 35 ].…”
Section: Introductionmentioning
confidence: 99%